A REVIEW STUDY ON ROLE OF CONTRACEPTIVES AND THEIR VARIOUS TYPES. - Deeksha; Ompi Kumari; Bharadwaj, Soumya (International Journal of Research -GRANTHAALAYAH, 2024)
Contraception is the process used to stop unwanted pregnancy and control birth rate. Contraceptives reduces the chances of pregnancy after sexual intercourse. Contraceptives prevent pregnancies by interfering with the procedure of fertilization. Contraceptives reduces the chances of abortion by preventing unintended pregnancies on their partners, in which 842 million (44%) are modern using modern methods of Contraceptives are accessible in huge varieties and types . Numerous contraceptives are available, 790 million (42%) are traditional method users according the statistical data of 2019. The most common contraceptive techniques that are use of contraceptives are increasing day by day, 922 million of women of reproductive age used worldwide are female sterilization and male condoms, female sterilization are used in 219 million users (24%), male condoms are used in 189 million users (21%) according the data of 2019. The use of traditional methods and IUDs has reduced worldwide since 1994. According to WHO, The only form of birth control is a condom,that can prevent both unintended pregnancies and sexually transmitted diseases. The need of family planning is increased globally up to 77% from 2015 to 2020.. Over the past 20 years, the number of women using family planning methods has grown, rising from 900 million in 2020 to 2000 million. Use of modern contraceptive methods is also increased from 663 million to 851 million with the prevalence rate of 47.7% to 49.0%. Numerous contraceptive methods exist, including hormonal methods like CHC vaginal ring, CHC transdermal patch, and combination hormonal contraceptives. Progestin-only techniques include hormonal male contraceptives, progestin-only pills, DMPA injections, implants, and progestin-only IUDs. The other approach is non-hormonal and consists of vaginal pH modulators, barrier techniques like condoms, and copper IUDs. Traditional methods, such as the LAM method, the fertile cycle method, and the withdrawal approach, comprise the third type of contraception. Herbal contraceptives, which use a variety of herbs and plant preparations, are the fourth technique of birth control.